2012
DOI: 10.1161/hypertensionaha.111.182220
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib-Induced Systemic Vasoconstriction in Swine Is Endothelin Mediated and Does Not Involve Nitric Oxide or Oxidative Stress

Abstract: Abstract-Angiogenesis inhibition with agents targeting tyrosine kinases of vascular endothelial growth factor receptors is an established anticancer treatment, but is, unfortunately, frequently accompanied by systemic hypertension and cardiac toxicity. Whether vascular endothelial growth factor receptor antagonism also has adverse effects on the pulmonary and coronary circulations is presently unknown. In chronically instrumented awake swine, the effects of the vascular endothelial growth factor receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 42 publications
7
78
1
Order By: Relevance
“…12 In a study performed in awake swine, the rise in BP induced by the NOS inhibitor N-nitro-l-arginine was increased after 1 week administration of sunitinib, causing a 12 mm Hg rise in mean arterial pressure, implying an increase rather than a decrease in NO availability. 38 Collectively, although not uniformly positive, the studies reviewed here support the view that VSP inhibition associates with a decrease in NO availability, contributing to the rise in BP.…”
Section: Mechanism Of Hypertension Decrease In No Bioavailabilitysupporting
confidence: 56%
See 2 more Smart Citations
“…12 In a study performed in awake swine, the rise in BP induced by the NOS inhibitor N-nitro-l-arginine was increased after 1 week administration of sunitinib, causing a 12 mm Hg rise in mean arterial pressure, implying an increase rather than a decrease in NO availability. 38 Collectively, although not uniformly positive, the studies reviewed here support the view that VSP inhibition associates with a decrease in NO availability, contributing to the rise in BP.…”
Section: Mechanism Of Hypertension Decrease In No Bioavailabilitysupporting
confidence: 56%
“…35 Likewise, in swine, the rise in BP induced by sunitinib could not be lowered by a cocktail of antioxidants, whereas the same cocktail lowered BP in sunitinib-naive animals. 38 Collectively, these observations do not support the idea that increased oxidative stress contributes to the development of hypertension induced by VSP inhibitors.…”
Section: Rarefaction and Oxidative Stress As Other Potential Hypertenmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent study in swine showed an increase in blood pressure within a few hours after administration of sunitinib, a tyrosine kinase inhibitor targeting the VEGF pathway. 16 The fast onset of changes in blood pressure makes rarefaction a less likely cause of VEGF targeting tyrosine kinase inhibitor-induced hypertension and suggests that rarefaction is a consequence rather than a cause of hypertension in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in NO bioavailability has been proposed as the mediating mechanism, however recent data in animals [74] and humans [75] suggests that angiogenesis inhibition results in substantial increases of ET-1 levels. Even more, a recent study reveals that hypertension is mediated by endothelin and not oxidative stress or NO [76]. Furthermore, ERAs prevented the development of hypertension during angiogenesis inhibition in rats [74,77].…”
Section: Eras In Antineoplastic Drugs-induced Hy-pertensionmentioning
confidence: 97%